PENGEMBANGAN INSTRUMEN PENILAIAN KETERAMPILAN PROSES BERBASIS DARING MELALUI DISCOVERY LEARNING PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN - Dian Rozalia Hapsari; Fatikhatun Nikmatus Sholihah (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
Assessment of process skills in online learning has not been optimally carried out because the instruments used are not suitable for online learning. The learning process becomes ineffective and students feel bored in following the learning. In MAN 7 Jombang it is known that the material for growth and development has never been assessed on process skills during online learning. Therefore, the material for growth and development is suitable for students to practice process skills. Educators at MAN 7 Jombang have never used an online-based process skills assessment instrument, so the authors developed an online-based process skills assessment instrument on growth and development materials. The development of this assessment instrument uses the 4D model, namely Define, Design, Develop, and Disseminate. However, the Disseminate stage was not implemented due to limited costs and time. The data collection instrument used a teacher needs analysis questionnaire, a student needs analysis questionnaire, an expert validation instrument assessment questionnaire, and a material expert validation questionnaire. The data analysis used the results of the validity questionnaire by the assessment instrument experts and the material was carried out descriptively. The results of the expert validation of the assessment instrument obtained an eligibility percentage of 75% with the proper criteria, and the results of the validation of the material experts obtained an eligibility percentage of 88.46% with very feasible criteria.